SORTING CAPABILITIES OF CASTINGS FROM NODULAR AND GRAY IRON BY THE STRUCTURE BY THE RESULT OF THE MEASUREMENT OF THE MAGNETIC PARAMETERS AND THE SPEED OF SOUND - S. G. Sandomirskiy; V. L. Zuckerman (Литьë и металлургия)
The results of the analysis of the influence of changes in the structure of the metal substrate and form of graphite inclusions in cast iron on the magnetic coercive sensitive parameter and the speed of sound are given. The efficiency of shared use of the results of magnetic and ultrasonic measurements to control the shape of inclusions in ductile iron and pearlite content in its metal matrix is shown.